Peer Coaching — Live Classroom In-service Teachers’ Training Programme - Anand, Ashutosh (THE PRIMARY TEACHER, 2016)
Peer coaching provides training to in-service teachers so that they can improve their teaching strategies while carrying out teaching–learning process in a class. For peer coaching, these in-service trainee–teachers, who may also be referred to as peer teachers, are required to visit a school, imparting training in teaching–learning strategies. The school serves as a training centre or model school. A teacher of this school may function as a coach and train these in-service teachers. A peer teacher is required to observe, cooperate, collaborate and evaluate oneself and other peer teachers under the guidance of the coach. After completion of the training, these peer teachers can also work as coaches.